Management analysis of dairy cow herd enterprises in the Kansas Farm Management Association - F.D. DeLano; Michael R. Langemeier (Kansas Agricultural Experiment Station Research Reports, 1994)
Actual records of dairy cow herd enterprises from Kansas Farm Management Association farms over the past 4 years have shown an increase in returns over variable costs from $17,900 to $27,000 per farm for a 100-cow dairy herd in favor of herds with higher milkproducing cows. Cost per hundred weight of milk produced per cow decreased for the higher-producing herds compared with lowerproducing herds, even though total cost per cow increased. In 1993, for every extra $1.00 spent on feed and other variable costs, the higher producing herds earned $2.34. This was a 234% return per dollar invested.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Economics; Dairy; Management